Sarcomeric Myosin Expression in the Tongue Body of Humans, Macaques and Rats - Rahnert, Jill A. (S. Karger AG, 2010)
Expression of developmental and unconventional myosin heavy chain (MHC) isoforms in some adult head and neck muscles is thought to reflect specific contractile demands of muscle fibers active during kinematically complex movements. Mammalian tongue muscles are active during oromotor behaviors that encompass a wide range of tongue movement speeds and tongue shape changes (e.g. respiration, oral transport, swallowing, rejection), but the extent to which tongue muscles express developmental and unconventional MHC is not known. Quantitative PCR was used to determine the mRNA content of conventional MHC-beta, MHC-2a, MHC-2b and MHC-2x, the developmental isoforms embryonic MHC and neonatal MHC and the unconventional isoforms atrial/cardiac-α MHC (MHC-alpha), extraocular MHC, masseter MHC and slow tonic MHC in tongue body muscles of the rat, macaque and human. In all species, conventional MHC isoforms predominate. MHC-2b and MHC-2x account for 98% of total MHC mRNA in the rat. MHC-2a, MHC-2x and MHC-beta account for 94% of total MHC mRNA in humans and 96% of total MHC mRNA in macaque. With the exception of MHC-alpha in humans (5%), developmental and unconventional MHC mRNA represents less than 0.3% of total MHC mRNA. We conclude that in these species, there is limited expression of developmental and unconventional MHC and that diversity of tongue body muscle fiber contractile properties is achieved primarily by MHC-beta, MHC-2a, MHC-2x and MHC-2b. Whether expression of MHC-alpha mRNA in tongue is unique to humans or present in other hominoids awaits further investigation.